PENGARUH PENERAPAN MODEL PEMBELAJARAN INKUIRI TERBIMBING TERHADAP KEMAMPUAN PEMAHAMAN KONSEP MATEMATIS SISWA KELAS VIII MTS AL ISLAM PETALABUMI - Fitri Ramadhani; Siska Aprilianingsih (Journal of Didactic Mathematics, 2020)
This study aims to determine the effect of the Implementation of Guided Inquiry Learning Model Against the Mathematical Understanding Ability of Class VIII Students of MTs Al Islam Petalabumi. The type of this research is Quasi Experiment research. The research design used was Randomized Subjects Posttest Only Control Group Design. The sampling technique is a purposive sampling technique. The instrument in this study was a test of students' mathematical concept comprehension ability. Data analysis techniques in this test use the Independent Samples T-Test. Based on the results of research testing the hypothesis of the two sample classes obtained P-value is smaller than a, which is 0,000 <0.05. This means that H0 is rejected and Ha is accepted. Thus the ability to understand students 'mathematical concepts with the application of guided inquiry learning models is better than the ability to understand students' mathematical concepts with conventional learning models.